Targeted in vitro- confirmation of the antiviral activity of Tenvir (Tenofovir) drug against the SARS-COV-2 virus variant B. in Kazakhstan and identifying NSP12 in the viral genome - Khaidarov, S.; Burashev , Y.; Kozhabergenov , N.; Usserbayev , B.; Melisbek , A.; Shirinbekov , M.; Moldakaryzova, A.; Beisenova , A.; Mustafaeva , A.; Kydyrbaeva , A. (Eurasian Journal of Applied Biotechnology, 2024)
COVID-19 became a true medication target worldwide due to its pandemic scale in 2020. Viral infections are generally hard to cope with, especially, if the viral load and spreading speed seriously surpass the immune reaction, both innate and adaptive. Thus, only relatively few drugs were used clinically to stop either in the early stages of viral reproduction like with the help of Tenvir (Tenofovir) or vaccination to gain collective immunity in a particular population. None of the interferon-based drugs showed clear medical effects in medical trials and during pandemic hospitalization protocols. However, purine-analogs like Tenvir and others showed sustainable survival and recovery rates among SARS-COV-2 virus-infected patients at moderate and severe stages of pneumonia caused by this virus. This article reveals the invitro testing of the Tenvir drug on virus strain, Variant B.1.1, Sampled from Kazakhstan and molecular-genetic characterization of NSP12 (non-structural protein 12) located in ORF1b region of the SARS-COV 2 genome. Tenvir or tenofovir was broadly used against HIV infection and this study shows a sufficient effect on viral spread due to RdRP-inhibiting properties in-vitro.